Distillation 2014
DOI: 10.1016/b978-0-12-386547-2.00011-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Distillation Processes

Abstract: In this work we present an overview of the main advances in column sequence optimization in zeotropic systems, ranging from systems using only conventional columns, each with a condenser and a reboiler, to fully thermally coupled systems with a single reboiler and a single condenser in the entire sequence. We also review the rigorous design of distillation columns, or column sequences. In all the cases we focus on mathematical programming approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…Distillation is an expensive operation, both in terms of investment and operating costs (183), yet its ubiquity testifies to its effectiveness as a separation method, even for non-ideal and azeotropic mixtures. As a result of its prominence and expense, many contributions have been made to improve its design and operation (184). A review of early techniques can be found in (185,186).…”
Section: Distillation Network Synthesismentioning
confidence: 99%
“…Distillation is an expensive operation, both in terms of investment and operating costs (183), yet its ubiquity testifies to its effectiveness as a separation method, even for non-ideal and azeotropic mixtures. As a result of its prominence and expense, many contributions have been made to improve its design and operation (184). A review of early techniques can be found in (185,186).…”
Section: Distillation Network Synthesismentioning
confidence: 99%
“…Nowadays, around 90–95% of separations and purifications are performed by distillation, a fact that is likely to change in the near future . The current membrane market share is about 2%, but this fraction is expected to increase .…”
Section: Introductionmentioning
confidence: 99%
“…2 Nowadays, around 90-95% of separations and purifications are performed by distillation, a fact that is likely to change in the near future. 3,4 The current membrane market share is about 2%, but this fraction is expected to increase. 5 In the case of gas separation, membrane systems compete with conventional technologies such as cryogenic distillation or pressure swing adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of logical relationships using Boolean or binary variables that can be included in a mathematical programming model, and that systematically include all the sequence of separation task that can be rearranged in N-1 distillation columns, was developed by Caballero and Grossmann in a set of papers -See for example, Caballero & Grossmann, (2014)-. As this model formulation does not rely on any specific column configuration, it is considered here as the starting point for generating intensified sequences.…”
Section: Introductionmentioning
confidence: 99%